1994
DOI: 10.1007/bf02059896
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation pheromone system of adult gregarious desert locust schistocerca gregaria (forskal)

Abstract: Six electrophysiologically active aromatic compounds, viz., anisole, benzaldehyde, veratrole, guaiacol, phenylacetonitrile, and phenol, were identified in the volatiles of older-adult male desert locust. Young adults and females of all age groups produced none or only trace quantities of these compounds. Comparison of the aggregation responses of young and older adults to the crude, older-adult, volatile extract and different synthetic blends of the six compounds showed that the aggregation pheromone system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 12 publications
10
107
2
Order By: Relevance
“…The increase in the amount of PAN from tissues with age correlated well with the earlier findings that showed increased headspace volatile amounts with age (Mahamat et al, 1993;Ferenz et al, 1994;Torto et al, 1994;Seidelmann et al, 2000). However, PAN was present in the body parts of both males and females although tissues from males contained 20-fold more PAN compared with the females.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The increase in the amount of PAN from tissues with age correlated well with the earlier findings that showed increased headspace volatile amounts with age (Mahamat et al, 1993;Ferenz et al, 1994;Torto et al, 1994;Seidelmann et al, 2000). However, PAN was present in the body parts of both males and females although tissues from males contained 20-fold more PAN compared with the females.…”
Section: Discussionsupporting
confidence: 87%
“…There was evidence of arrestment (Torto et al, 1994) of individuals closer to a PAN source at low relative doses but repellent characteristics (Seidelmann and Ferenz, 2002) at higher doses. It is possible that, accumulating high concentrations of PAN could be toxic to the locusts hence it appears the locusts have developed a mechanism to disperse it rapidly from the body tissues.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is widely used in flavors such as almond and cherry in various fragrances for soaps and toiletries, in the pharmaceutical production, aromatic alcohols, photographic chemicals and others (9). In the context of using by its aromatic property, Torto et al (10) reported the application of benzaldehyde and five others aromatic compounds as aggregation pheromone system to young and older adult gregarious desert locust Schistocerca gragaria. Leal et al (11) reported the application of benzaldehyde as alarm pheromone to the acarid mite Tyrophagus perniciosus.…”
Section: Issn: 2320-5407mentioning
confidence: 99%